REVISITING GROUP WORK METHOD IN THE CONTEXT OF NON-FORMAL EDUCATION - Vintere, Anna; Ozola, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The use of group work in non-formal education has been practiced for many years. Researchers mention that group work may be mutually beneficial for learners in terms of the acquired knowledge, however, group work participants might be carried away by dealing with relationships within the group. In recent years, various international projects of training courses for youth and adult educators choose learner-centred group work or workshop format instead of traditional teacher-centred lecturing style. Also, generation of millennials who are digital residents and are more accustomed to technologies and telephones than face-to-face interaction requires more detailed preparing of the activities of the group work. Young adults prefer to work with facilitators who are approachable, supportive, good communicators, and good motivators. According to the previous research results, during the work group learners develop critical thinking skills, time management skills, team work and presentation skills, tolerance and other skills. The present paper is an attempt to research the strengths and weaknesses of the group work method in non-formal education in the framework of two international project activities: Nordplus adult education project “Design thinking method for creative tackling unemployment” and international youth training of Erasmus+ project "You(th)r Culture". The conclusion gives the summary of the findings of the research, focusing on the benefits of using of the group work method for the multinational audience of adult educators and youth, as well as identifying the main differences in its implementation for the relevant audiences.